microRNA-Dependent Modulation of Genes Contributes to ESR1's Effect on ERα Positive Breast Cancer - Gao, Shan; Ding, Bisha; Lou, Weiyang (Frontiers in Oncology, 2020)
Background: Dysregulation of ESR1 accounts for endocrine therapy resistance and metastasis of ERα positive breast cancer. However, the underlying molecular mechanism of ESR1 in ERα positive breast cancer remains insufficiency. Notably, to date, a comprehensive miRNA-mRNA regulatory network involved in modulation of ESR1 in development and progression of ERα positive breast cancer is still not established. Methods: Microarray miRNA and mRNA expression profiling from GEO database were used to obtained significant DE-miRNAs and DE-mRNAs in ERα positive breast cancer. Functional enrichment analysis was conducted by Enrichr database. STRING database was utilized to construct protein-protein interaction network, after which hub genes were identified through Cytoscape. Kaplan-Meier plotter was introduced to perform survival analysis. The relationship between ESR1-miRNA or miRNA-target gene pairs were experimentally validated. Results: 74 DE-miRNAs, including 19 upregulated and 55 downregulated miRNAs, and 830 DE-mRNAs, including 359 upregulated and 471 downregulated mRNAs, in ERα positive breast cancer were identified. Potential DE-mRNAs were statistically enriched in several cancer-associated pathways, such as cell cycle and pathway in cancer. 51 hub genes with node degree more than 10 were screened. 27 of 51 hub genes had significant prognostic values in ERα positive breast cancer. Based on the 27 hub genes, a miRNA-hub gene network, containing 26 miRNAs, was established. 7 of 26 miRNAs were found to possess prognostic predictive roles for patients with ERα positive breast cancer by combination of TCGA and METABRIC data. Intriguingly, ESR1 positively correlated and regulated the 7 miRNAs and the 7 miRNAs inversely correlated and modulated their corresponding downstream targets in MCF-7 and T47D cells, supporting the accuracy of in silico analysis. The relationship between ESR1-miRNA, miRNA-mRNA or ESR1-mRNA pairs was validated in clinical ERα positive breast cancer. Conclusions: In total, the current findings from this work add substantially to the understanding of ESR1’s molecular regulatory mechanism in ERα positive breast cancer.